أثر برنامج تدريبي مستند إلى نظرية قيمة الذات في رفع الكفاية الأكاديمية لدى طلبة المرحلة الثانوية - الجراح، أمل حسين سعيد; العتوم، عدنان يوسف (جامعة إربد الأهلية - عمادة البحث العلمي, 2023)
هدفت هذه الدراسة إلى الكشف عن أثر برنامج تدريبي مستند إلى نظرية قيمة الذات في رفع الكفاية الأكاديمية لدى طلبة المرحلة الثانوية. ولتحقيق أهداف الدراسة، تم اختيار عينة مكونة من (64) طالبة من طالبات الصف الأول ثانوي في مدرسة ثانوية اربد الشاملة للبنات، وجرى توزيعهن عشوائيا ومناصفة إلى مجموعتين: تجريبية وتحتوي (32) طالبة، وضابطة وتحتوي (32) طالبة، طبق على المجموعتين مقياس الكفاية الأكاديمية، وعلى المجموعة التجريبية البرنامج التدريبي. أظهرت النتائج عدم وجود فروق دالة إحصائيا عند (0.05 = α) في توزيع مستويات الكفاية الأكاديمية في القياس القبلي للمجموعتين، ووجود أثر دال إحصائيا للبرنامج التدريبي في تحسين الكفاية الأكاديمية بمجالاتها الستة لدى أفراد المجموعة التجريبية، ووجود أثر للبرنامج في القياس التتبعي في تحسين مستوى الكفاية الأكاديمية بمجالاتها الستة لدى أفراد المجموعة التجريبية. This study aimed to reveal the effect of a training program based on self-worth theory in raising the academic competence of secondary school students. To achieve the objectives of the study, a sample of (64) female students was selected from the first of secondary class in Irbid Comprehensive Secondary School for girls, and then distributed randomly and equally into two groups: experimental, containing (32) female students, and control, containing (32) female students. The academic competency scale was used for the two groups, while the control group was subjected to the training program. The results showed that there were no statistically significant differences at (α = 0.05) in the distribution of the levels of the academic competence in the pre-measurement for the two groups, while there was a statistically significant effect of the training program in improving the students’ academic competence in its six areas among members of the experimental group, and there was an effect of the program in the follow-up measurement in improving the level of the academic competence in its six areas among members of the experimental group. This study aimed to reveal the effect of a training program based on self-worth theory in raising the academic competence of secondary school students. To achieve the objectives of the study, a sample of (64) female students was selected from the first of secondary class in Irbid Comprehensive Secondary School for girls, and then distributed randomly and equally into two groups: experimental, containing (32) female students, and control, containing (32) female students. The academic competency scale was used for the two groups, while the control group was subjected to the training program. The results showed that there were no statistically significant differences at (α = 0.05) in the distribution of the levels of the academic competence in the pre measurement for the two groups, while there was a statistically significant effect of the training program in improving the students’ academic competence in its six areas among members of the experimental group, and there was an effect of the program in the follow-up measurement in improving the level of the academic competence in its six areas among members of the experimental group.
Keywords: القيمة الذاتية -- تقدير الذات -- الكفاءة الأكاديمية -- طلبة المرحلة الثانوية